2001
DOI: 10.1109/32.910861
|View full text |Cite
|
Sign up to set email alerts
|

An empirical study using task assignment patterns to improve the accuracy of software effort estimation

Abstract: In most software development organizations, there is seldom a one-to-one mapping between software developers and development tasks. It is frequently necessary to concurrently assign individuals to multiple tasks, and to assign more than one individual to work cooperatively on a single task. A principal goal in making such assignments should be to minimize the effort required to complete each task. But what impact does the manner in which developers are assigned to tasks have on the effort requirements? This pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(46 citation statements)
references
References 20 publications
0
45
0
Order By: Relevance
“…Also capabilities of the team members in terms of project complexity and risk factors to be measured. After that we can focus on estimating the total cost of the product and as a result we can schedule the product [2,[4][5][6][7].…”
Section: Methodology For Estimation With Machine Learningmentioning
confidence: 99%
See 3 more Smart Citations
“…Also capabilities of the team members in terms of project complexity and risk factors to be measured. After that we can focus on estimating the total cost of the product and as a result we can schedule the product [2,[4][5][6][7].…”
Section: Methodology For Estimation With Machine Learningmentioning
confidence: 99%
“…With high objective the organizations may establish the service level agreements for resolving issues. The targets pertain to factors that will measure the effectiveness of the system [6].…”
Section: Expected Outcome With Data Analyticsmentioning
confidence: 99%
See 2 more Smart Citations
“…First, hybrid estimation method exists [153]. Second, while the majority of studies confirmed the effect of group size on software development effort, Smith et al [174] showed the effect was not always statistically significant. Finally, optimality does not mean sticking to the same group size over the entire project lifespan.…”
Section: More Useful Discoveriesmentioning
confidence: 99%